Поведінка обміну знаннями: критичне мислення, наслідки і майбутнє - Suryantini, Ni Putu Santi; Darmayanti, Ni Putu Ayu; Arsawan, I Wayan Edi (Dr. Viktor Koval, 2020)
Introduction. Entering the industrial revolution 4.0 and society era 5.0, organizations are required to develop themselves based on intensive knowledge management. Organizations need, capture and represent knowledge, exchange and reuse it for different processes and applications, virtually creating an appropriate environment that stimulates the transfer and use of knowledge. This study provides insight into the importance of sharing knowledge in organizations while providing critical thinking to existing literature so that it can provide a new perspective in researching knowledge sharing. Aims and Task. The purpose of this study is to provide a structured and detailed analysis and knowledge map of knowledge-sharing practices based on approaches that can be used as the basis for research and analysis contributes to the importance of knowledge-sharing for improving the quality of team and organization management. Result. This study presents four gap management practices that can be used as a basis in research and analysis, contributing to the importance of sharing knowledge to improving the quality of management in teams and organizations. The first gap is about elaboration theory between resource-based view and social exchange theory, second about the divergence of the results of empirical studies where research on antecedents of knowledge sharing is mostly done at large companies, third is the substance of the practice of knowledge sharing in an organization, and fourth is the capability of human resources in conducting knowledge sharing practices. Conclusion. This research provides insight that knowledge sharing is a crucial element for the development of individuals, teams, and organizations. Knowledge plays an important role in intellectual capital inventory that can be used as knowledge creation, which is useful in improving employee competitiveness and skills, increasing manager's analysis of change and turbulence, improving business performance and competitive advantage of organizations to build superior performance. Future research is to examine the relationship of knowledge sharing with variables of organizational behavior, psychology, human resource practices, and strategic management.